The International Student's Voice: can it make a difference? Enhancing the International Student's Learning Experience - Catherine Riley (Pensa MultiMedia, 2014)
While Quality Assurance and Enhancement (QA&E) practices and processes have been at the heart of the Higher Education debate across Europe for over 20 years (Harvey and Williams, 2010), Italian universities have only recently (2013) begun to implement (with some resistance) compulsory external QA&E mechanisms (ANVUR)1. Any attempt to enhance the learning experience in HE is welcome, in particular those which promote excellence in teaching, but whether these external processes (ENQA, 2009)2 will have the desired impact remains to be seen (cfr Henard & Roseveare, 2012). Indeed, studies have shown (e.g. Greere & Riley in print, Harvey & Williams, 2010) that even in countries where such mechanisms have long been the norm and external quality processes (QA) have become ritualised, there is little evidence that this has translated into the creation of a quality culture, actively engaging all stakeholders (students, teachers, administrators and quality managers) in promoting quality (QE) (Räsänen, 2013). Indeed, while there have long been calls for the development of a quality culture 'on the ground' (EUA, 2006; ENQA, 2009; Vettori, 2012), the literature lacks reports of successful bottom-up practices which result in such a culture. This study will present one such case study. Thanks to the election of an international student on the Student-Teacher Committee at the School of International Studies, a need to address issues specifically regarding international students emerged. As part of the EU funded SPEAQ project (Sharing Practices to Enhance and Assure Quality), a micro-project was thus developed which would engage international students in identifying possible actions and initiatives to address these issues. While the project aimed to enhance the learning experience of International Students through